Energy saving synergies in national energy systems. (October 2015) - Thellufsen, Jakob Zinck; Lund, Henrik
Highlights: A systems approach is suggested when investigating the benefits of energy savings. The effect of savings is analysed on a Danish case. Synergies between different types of savings are investigated. System effects can be very significant for the performance of savings. Different types of energy savings must be coordinated. Abstract: In the transition towards a 100% renewable energy system, energy savings are essential. The possibility of energy savings through conservation or efficiency increases can be identified in, for instance, the heating and electricity sectors, in industry, and in transport. Several studies point to various optimal levels of savings in the different sectors of the energy system. However, these studies do not investigate the idea of energy savings being system dependent. This paper argues that such system dependency is critical to understand, as it does not make sense to analyse an energy saving without taking into account the actual benefit of the saving in relation to the energy system. The study therefore identifies a need to understand how saving methods may interact with each other and the system in which they are conducted. By using energy system analysis to do hourly simulation of the current Danish energy system, the combination of reductions in heat and electricity demands is analysed within the Danish district heating sector to show the benefits of coordinating savings in the electricity and district heating sectors.